Comparative Study of Guava Leaf Bioactive Extracts Using Ultrasonication Assisted Extraction - Khanna, Somya; Singh, Pragati; Chauhan, Ekta Singh (Biomedical Sciences and Clinical Medicine, 2025)
Objective Guava (Psidium guajava L.), a member of the Myrtaceae family, is grown worldwide and is widely consumed in India because of its good nutritional value as well as its medicinal properties. various parts of the guava tree, e.g., its root, bark, leaves, and fruit, have been found to be rich in pharmacological properties. Despite the health benefits, parts of the tree other than the guava fruit are not widely used by people. Guava leaves are generally considered as a non-conventional food with high nutritive value, medicinal properties, essential oils and good amounts of bioactive compounds. Methods In this study, these bioactive compounds were extracted by ultrasound-assisted extraction (UAE) using three different solvents (water, ethanol and methanol) and the extracts were tested for finding the bioactive content in it. Results This study found that dilute methanol (50 : 50) extracts contain significant amounts of flavonoids, alkaloids, saponins and terpenoids. Ethanol extracts showed good quantities of tannins and aqueous extract showed good extraction of total phenolic content. Conclusions These findings show that guava leaves are rich in bioactive compounds which can be extracted using environmentally friendly methods which can be used in food and pharmaceutical industries